In vitro models of intracerebral hemorrhage - Bilal Syed; Abhijit Nirwane; Yao Yao (Brain Hemorrhages, 2022)
Intracerebral hemorrhage (ICH) is a severe clinical emergency caused by bleeding into brain parenchyma. Currently, there are no effective treatments to improve ICH outcomes. Developing new therapies for ICH relies on a thorough understanding of ICH pathophysiology and good in vitro models that enable mechanistic research. In this review, we summarize commonly used in vitro ICH models and compare their advantages and disadvantages. Next, key questions that need to be answered in future research are discussed. We aim to provide a quick reference/summary of widely used in vitro ICH models and stimulate the development of new models.